2018
DOI: 10.1007/s00429-018-1696-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrotonic signal processing in AII amacrine cells: compartmental models and passive membrane properties for a gap junction-coupled retinal neuron

Abstract: Amacrine cells are critical for processing of visual signals, but little is known about their electrotonic structure and passive membrane properties. AII amacrine cells are multifunctional interneurons in the mammalian retina and essential for both rod- and cone-mediated vision. Their dendrites are the site of both input and output chemical synapses and gap junctions that form electrically coupled networks. This electrical coupling is a challenge for developing realistic computer models of single neurons. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 74 publications
1
37
0
Order By: Relevance
“…Gap junction properties include high speed, bidirectional and reliable communication between neurons, while a single gap junction is able to both inhibit and excite a postjunctional target. These features represent distinct advantages of gap junctions over chemical synapses [68][69][70][71][72][73] .…”
Section: Gap Junctions and Oscillation Frequencymentioning
confidence: 99%
“…Gap junction properties include high speed, bidirectional and reliable communication between neurons, while a single gap junction is able to both inhibit and excite a postjunctional target. These features represent distinct advantages of gap junctions over chemical synapses [68][69][70][71][72][73] .…”
Section: Gap Junctions and Oscillation Frequencymentioning
confidence: 99%
“…One mechanism involves direct spillover of synaptically released glutamate, and the other mechanism involves activation by ambient glutamate. With respect to the first mechanism, there is evidence that glutamate spillover at the rod bipolar cell axon terminal can activate glutamate transporters on the same and neighboring axon terminals (Veruki et al, 2006;Wersinger et al, 2006). Depending on their exact location, this suggests that NMDA receptors on AII and A17 amacrine cells under certain conditions could be activated by spillover of glutamate from rod bipolar cells after synaptic release.…”
Section: Ambient Glutamate Can Activate Nmda Receptors On Both Aii Anmentioning
confidence: 99%
“…We next examined whether the increased activity of glutamate transporters at a more physiological temperature would reduce the level of ambient glutamate and/or prevent spillover of synaptic glutamate (Wadiche et al, 1995;Asztely et al, 1997;Rauen et al, 1998) and thus reduce or eliminate the observed NMDA receptor-mediated membrane noise. When we repeated these experiments for AII amacrine cells at 32°C, the average variance in the control condition was 57.7 Ϯ 15.4 pA 2 ; and in the presence of CPP, it was 39.3 Ϯ 11.7 pA 2 ( p ϭ 0.0223, paired t test; n ϭ 5 cells; Fig.…”
Section: Ambient Glutamate Can Activate Nmda Receptors On Both Aii Anmentioning
confidence: 99%
“…There are some approaches that feature a detailed description of a specific neuron. A clear limitation of this approach corresponds to the large number of parameters in the model [24][25][26][27]. Many of these parameters represent unknown variables, which is typical from such high-dimensional problems that include the description of dynamics of a variety of often spatially dependent ion channels along the dendritic tree.…”
Section: Introductionmentioning
confidence: 99%